Guia corporativo empresarial - CASSINHA, Joana Coelho Guimarães; SOUZA, Nicolas Matheus Martins de; REIS, Sabrina Clara da Silva (026, 2024)
O artigo apresenta o desenvolvimento do layout fotográfico do “Guia corporativo empresarial” com o intuito de dar visibilidade a pequenos esteticistas de Guaratinguetá-SP. Além de encarar a ocorrência de novos negócios e de empresas bem-sucedidas, eles têm de lidar com os desafios de gestão de pessoas e a alta carga tributária do país. A produção do projeto foi decidida e feita a partir de pesquisas bibliográficas e circunstâncias ocorridas no dia a dia.

The article presents the development of the photographic layout of the “Corporate Business Guide” with the aim of giving visibility to small beauticiansin Guaratinguetá-SP. In addition to facing the emergence of new businesses and also successful companies, they have to deal with the challenges of people management and the country's high tax burden. The production of the project was decided and carried out based on bibliographic research and circumstances that occur in everyday life.
Corporate Business Guide
Keywords: Layout; Negócios; Estética; Produção Cultural e Design